Racism without racists - Bonilla-Silva, Eduardo (Rowman & Littlefield Publishers, Inc., 2014)
The fourth edition adds a chapter on what Bonilla-Silva calls "the new racism," which provides the essential foundation to explore issues of race and ethnicity in more depth. This edition also updates Bonilla-Silva’s assessment of race in America after President Barack Obama’s re-election. Obama’s presidency, Bonilla-Silva argues, does not represent a sea change in race relations, but rather embodies disturbing racial trends of the past